module Cat.Displayed.Cartesian.Right
  {o  o′ ℓ′}
  { : Precategory o }
  ( : Displayed  o′ ℓ′)

open Cat.Reasoning 
open Displayed 
open Cat.Displayed.Cartesian 
open Cat.Displayed.Morphism 
open Cat.Displayed.Reasoning 

Right Fibrations🔗

A cartesian fibration E\mathcal{E} is said to be a right fibration if every morphism in E\mathcal{E} is cartesian.

record Right-fibration : Type (o    o′  ℓ′) where
    is-fibration : Cartesian-fibration
      :  {x y} {f : Hom x y}
        {x′ y′} (f′ : Hom[ f ] x′ y′)
       is-cartesian f f′

  open Cartesian-fibration is-fibration public

One notable fact is every vertical morphism of a right fibrations is invertible. In other words, if E\mathcal{E} is a right fibration, then all of its fibre categories are groupoids. This follows directly from the fact that vertical cartesian maps are invertible.

  : Right-fibration
    {x} {x′ x″ : Ob[ x ]}  (f′ : Hom[ id ] x′ x″)  is-invertible↓ f′
right-fibration→vertical-invertible rfib f′ =
  vertical+cartesian→invertible (Right-fibration.cartesian rfib f′)

More notably, this is an exact characterization of categories fibred in groupoids! If E\mathcal{E} is a cartesian fibration where all vertical morphisms are invertible, then it must be a right fibration.

  : Cartesian-fibration
   (∀ {x} {x′ x″ : Ob[ x ]}  (f′ : Hom[ id ] x′ x″)  is-invertible↓ f′)
vertical-invertible+fibration→right-fibration fib vert-inv = fib
vertical-invertible+fibration→right-fibration fib vert-inv
  .Right-fibration.cartesian {x = x} {f = f} {x′ = x′} {y′ = y′} f′ = f-cart where
    open Cartesian-fibration fib
    open Cartesian-lift renaming (x′ to x-lift)

To see this, recall that cartesian morphisms are stable under vertical retractions. The cartesian lift ff^{*} of ff is obviously cartesian, so it suffices to show that there is a vertical retraction xxx^{*} \to x'. To construct this retraction, we shall factorize ff' over fidf \cdot id; which yields a vertical morphism i:xxi^{*} : x' \to x^{*}. By our hypotheses, ii^{*} is invertible, and thus is a retraction. What remains to be shown is that the inverse to ii^{*} factors ff' and ff^{*}; this follows from the factorisation of ff' and the fact that ii^{*} is invertible.

    x* : Ob[ x ]
    x* = has-lift f y′ .x-lift

    f* : Hom[ f ] x* y′
    f* = has-lift f y′ .lifting

    module f* = is-cartesian (has-lift f y′ .cartesian)

    i* : Hom[ id ] x′ x*
    i* = f*.universal′ (idr f) f′

    module i*-inv = is-invertible[_] (vert-inv i*)

    i*⁻¹ : Hom[ id ] x* x′
    i*⁻¹ = i*-inv.inv′

    factors : f′ ∘′ i*⁻¹ ≡[ idr f ] f*
    factors = to-pathp⁻ $
      f′ ∘′ i*⁻¹               ≡⟨ shiftr _ (pushl′ _ (symP $ f*.commutesp (idr f) f′) {q = ap (f ∘_) (sym (idl _))}) 
      hom[] (f* ∘′ i* ∘′ i*⁻¹) ≡⟨ weave _ (elimr (idl id)) _ (elimr′ _ i*-inv.invl′) 
      hom[] f* 

    f-cart : is-cartesian f f′
    f-cart = cartesian-vertical-retraction-stable
      (has-lift f y′ .cartesian)
      (inverses[]→from-has-section[] i*-inv.inverses′)

As a corollary, we get that all discrete fibrations are right fibrations. Intuitively, this is true, as sets are 0-groupoids.

  : Discrete-fibration 
discrete→right-fibration dfib =
    (discrete→cartesian  dfib)
    (discrete→vertical-invertible  dfib)

Fibred Functors and Right Fibrations🔗

As every map in a right fibration is cartesian, every displayed functor into a right fibration is automatically fibred.

  :  {o₂ ℓ₂ o₂′ ℓ₂′}
   {𝒟 : Precategory o₂ ℓ₂}
   { : Displayed 𝒟 o₂′ ℓ₂′}
   {F : Functor 𝒟 }
   (F′ : Displayed-functor   F)
   Fibred-functor   F
functor+right-fibration→fibred rfib F′ .Fibred-functor.disp =
functor+right-fibration→fibred rfib F′ .Fibred-functor.F-cartesian f′ _ =
  Right-fibration.cartesian rfib (F₁′ f′)
  where open Displayed-functor F′

Specifically, this implies that all displayed functors into a discrete fibrations are fibred. This means that we can drop the fibred condition when working with functors between discrete fibrations.

  :  {o₂ ℓ₂ o₂′ ℓ₂′}
   {𝒟 : Precategory o₂ ℓ₂}
   { : Displayed 𝒟 o₂′ ℓ₂′}
   {F : Functor 𝒟 }
   (F′ : Displayed-functor   F)
   Fibred-functor   F
functor+discrete→fibred disc F′ =
  functor+right-fibration→fibred (discrete→right-fibration disc) F′